Positronium formation in positron-Li and positron-Na collisions at low energies - Le, Anh-Thu; Bromley, M. W. J.; Lin, C. D. (My University, 2005)
We present the positronium formation cross sections for a positron colliding with lithium and sodium for the collision energies from 0.01eV up to 20eV by the hyperspherical close-coupling method. For Li, our results agree with the experimental data and with other calculations. Our results for Na remain in agreement with previous close-coupling calculations, but do not support the latest experimental data for Na below 1eV. To validate our model potentials and method in the low-energy regime, the binding energies of positronic lithium and positronic sodium as well as the s-wave scattering lengths for positronium scattering from Li+ and Na+ are also presented.